2017
DOI: 10.2337/db16-0839
|View full text |Cite
|
Sign up to set email alerts
|

dUTPase (DUT) Is Mutated in a Novel Monogenic Syndrome With Diabetes and Bone Marrow Failure

Abstract: We describe a new syndrome characterized by early-onset diabetes associated with bone marrow failure, affecting mostly the erythrocytic lineage. Using whole-exome sequencing in a remotely consanguineous patient from a family with two affected siblings, we identified a single homozygous missense mutation (chr15.hg19:g.48,626,619A>G) located in the dUTPase () gene (National Center for Biotechnology Information Gene ID 1854), affecting both the mitochondrial (DUT-M p.Y142C) and the nuclear (DUT-N p.Y54C) isoforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Previous studies have shown that dUTPase regulation plays a vital role in programmed cell death in Drosophila, yeast and mammalian cells (29,30). Furthermore, a dysfunctional dUTPase causes a novel monogenic syndrome that leads to diabetes and bone marrow failure (31). Similarly, the dUTPases of many viruses, including poxviruses, herpesviruses, and several vertebrate retroviruses, play important roles in efficient virus replication; therefore, mutations in the dUTPase sequence can significantly affect the biological and pathogenic properties of these viruses (32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Previous studies have shown that dUTPase regulation plays a vital role in programmed cell death in Drosophila, yeast and mammalian cells (29,30). Furthermore, a dysfunctional dUTPase causes a novel monogenic syndrome that leads to diabetes and bone marrow failure (31). Similarly, the dUTPases of many viruses, including poxviruses, herpesviruses, and several vertebrate retroviruses, play important roles in efficient virus replication; therefore, mutations in the dUTPase sequence can significantly affect the biological and pathogenic properties of these viruses (32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…It has also been shown that dUTPase overexpression in cancers decrease the effectivity of thymidylate-synthase targeted chemotherapy (e. g. 5-fluorouracil, methotrexate) 54 57 and is involved in development of resistance against the treatment 58 , 59 . Interestingly, a human dUTPase mutation (Tyr54Cys) located outside the conserved region was suggested to be responsible for monogenic syndrome associated with diabetes type 2 and bone marrow failure 53 . This report was the first and to date the only case where a dUTPase mutation has been associated with human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although the supportive evidence presented in this study is overwhelmingly genetic in nature, we also share experimental evidence in support of the pathogenesis of the missense variant identified in DUT. Since the case reported by Dos Santos et al (2017), no follow up studies have been published on the involvement of DUT in the pathogenesis of the syndrome of diabetes with bone marrow failure. Without functional validation, the novel missense variant we encountered in a patient with that syndrome will not have much weight due to lack of compelling segregation.…”
Section: Discussionmentioning
confidence: 99%